Validation of The Academic Success Instrument Using Polytomous Item Response Theory - Ahmad, Hishamuddin; Mokshein, Siti Eshah; Husin, Mohd Razimi; Panessai, Ismail Yusuf; Zabita, Mohd Nazir Md; Ghazali, Nor Hasnida Che Md (International Journal of Psychosocial Rehabilitation, 2020)
Several instruments that measuring an academic success have been developed and published. However, a psychometrically sound instrument to measure academic success that suitable for the Malaysian context needs to be validated. Therefore, this study aimed to validate on Academic Success Inventory for College Students (ASICS) instrument which contains 49 items in Malaysian context. The sample comprised 305 students from three schools. Data was analyzed based on the Polytomous Item Response Theory (IRT) using the Xcalibre software. Based on the chi-square, p-value, and the -2 LogLikelihood, Samejima's Graded Rating Model was found to be the most fit model with the data. Unidimensionality assumption and local independence were tested using the exploratory factor analysis and were fulfilled. The instrument’s reliability was overall very satisfactory (α=0.89) and the construct validity was also fulfilled with the value of 0.86. Therefore, this instrument adds to the limited collection of locally validated instruments in the field of educational assessment and evaluation.